Effects of Mesona chinensis Benth polysaccharide on physicochemical and rheological properties of sweet potato starch and its interactions. (February 2020) - Ren, Yanming; Jiang, Lian; Wang, Wenjie; Xiao, Yuehuan; Liu, Suchen; Luo, Yu; Shen, Mingyue; Xie, Jianhua
Abstract: Polysaccharides are used in starch-based product formulations during processing for improving the final quality of foods. The effects of polysaccharide-starch interactions on the physicochemical and rheological properties of sweet potato starch (SPS)– Mesona chinensis Benth polysaccharide (MCP) gels were investigated. Results showed that MCP can significantly increase the peak viscosity, breakdown and setback viscosity. Rheological determination results suggested that SPS–MCP gels exhibited shear-thinning behavior and that MCP can effectively enhance the viscoelasticity of SPS–MCP gels. Interaction force test indicated hydrogen bonding and electrostatic force can enhance the gel strength and hardness of SPS–MCP gels. Particle size distribution suggested that MCP can enlarge the size of SPS–MCP gels. Fourier-transform infrared spectroscopy (FT–IR) results suggested that the interactions between SPS and MCP involving intermolecular hydrogen bonding and no covalent bonding. In addition, MCP at a suitable concentration can improve the microstructure of SPS–MCP gels. These results facilitate the development of SPS–based products and understand the interaction mechanism between SPS and MCP. Graphical abstract: Image 1 Highlights: MCP enhances pasting, apparent viscosity and dynamic modulus of SPS-MCP gels. Interactions of SPS-MCP are likely to be hydrogen bond and electrostatic force. MCP improves gel properties and enlarges particle size of SPS-MCP gels. MCP improves the microstructure of SPS-MCP gels at 0.05% concentration.